Antidiabetic Properties of Chandraprabha Vati - Sakshi Bhardwaj; Shailza Bhatnagar; Kalpana Yadav; Pankaj Yogi; Pooja Yadav; Deepak Jangidh; Ambika (AYUSHDHARA, 2024)
Diabetes mellitus is a group of metabolic disorders characterized by elevated blood glucose levels and symptoms like polyuria, polydipsia and polyphagia. It arises from insufficient insulin secretion, insulin resistance, or both. Ayurveda mentions this disease as Prameha. Chandraprabha vati is an effective formulation widely used in its management. It is an Ayurvedic formulation available in classical Vati form. The indications of Chandraprabha vati include Prameha and its complications like Vibandha (constipation), Anaha (distension of abdomen due to obstruction to passage of urine and stools), Kustha (diseases of skin), Netra roga (eye disorder) etc. It contains 37 herbomineral ingredients which exhibit various actions. The Rasayana, Vrishya, Shothhara, Deepana paachana and Vatanulomana karma are present in this formulation which makes it a drug of choice in chronic cases of Prameha as add on therapy to regular treatment. All the ingredients possess anti-diabetic activity. The article discusses about its role in the management of Prameha in detail.